(untitled) (Comprehensive Journal of Science, 2025)
History is the sum total of human experience in civilization، culture، and the city. Civilization in terms of politics، ethics، and legislation is the organizational force of history، culture in terms of science، literature، and art is the creative force of history، and the city in terms of agriculture، industry، and architecture is the commodity material force of history، In fact، the human fondness for knowing what happened in the past has been associated with the aspiration not only to know what happened، but also why and how it happened. The idea of history for any human group is in fact a form of this group’s understanding of its own identity، and the development of historical knowledge has remained connected to the development of human knowledge in general and scientific knowledge in particular. Frederick Hegel commented that the basic field of history is life in its temporal extension on earth. Historians have differed in their perceptions of historical time، and their theories have varied with regard to presenting their view of the course of this time as a whole، The most famous of them are the realization of the will of God، as in the case of St. Augustine، the evolution towards a free society، as in the case of Friedrich Hegel، the realization of a classless society، as in the case of Karl Marx، or the civilizational cycle، as in the case of Abd al-Rahman Ibn Khaldun، Battista Vico، Oswald Spengler، Arnold Toynbee، and many others. Translated with DeepL.com (free version).